INFLUENCE OF DIAGNOSTICALLY-DETERMINED CLINICAL DECISIONS ON A TREATMENT IN PATIENTS WITH MANDIBULAR PARTIAL TEETH LOSS - R. Bratus-Hrynkiv (Ukrainian Medical Stomatological Academy, 2016)
According to numerous scientific studies patients with mandibular partial teeth loss need fixed, removable or combined dentures. It is determined by topography of toothless areas, abutment teeth status, presence of occlusal pairs and status of alveolar bone and mucous membrane [1,2,3,4,5]. Comprehensive analysis of the clinical situation with the main classification criteria (E.Kennedy 1928, K. Eichner 1955, E. Korber 1987, AI Betelman, 1952), and individual characteristics are the basis not only for the proper formulation of diagnosis but adequate prognostic assessment [6, 7, 8, 9]. High frequency of various types of disadvantages that cause complications and inapplicability of dentures has not been observed yet, so the actual task is a reasonable choice of treatment plan and its impact on patient's health. [10,11,12,13]. Such measures as diagnostics, prevention and treatment of partial teeth loss with use of local and standardized protocols are used in order to satisfy human needs for dental health maintenance and recovery [14]. The aim of the investigation is to identify the causes and find possibilities to prevent complications when mandibular removable dentures are used. 58 patients were involved in the investigation (30 women and 28 men) aged 50-76 years who presented inability to use partial removable acrylic and cast-based dentures (partial) -37 (63.8% patients) or complete overdentures (overdentures) - 21 (46.2% patients), during such period of time: from 4 to 42 months. Complaints of cracks and fractures of the basis (15 patients -25.9%), fixing impairment (13 people -22.4%), the destruction of the abutment teeth (18 patients-31.0%), and injuries of oral tissues by the denture (12 people 20,7%) were observed. Among the factors that can cause complications and disadvantages when prostheses were used in patients with single remaining teeth are often determined: anatomical (atrophy of alveolar bone and mucous membrane), clinical (denture stability interruption), mistakes during laboratory stages of manufacturing dentures and patient's difficult adaptation to a dentures [13]. Instead, the process of treatment plan has not been observed by most researchers. Only 7 (12.1%) cases of dental patient records of the diagnosis using code of ICD-10 were detected, but block K08.4. was not used by anyone. The most common complication -18 (31.0%) of observations was the destruction of the supporting/abutment teeth in patients with partial dentures in 14 (24.1%) cases, using overdentures - in 4 (6.9%) cases. The second reason of patients references were cracks and fractures of the denture basis in 15 (25.9%) of observations using overdentures in 8 (13.8%) cases. 7 (12.0% ) of cases presented patients with partial dentures. Complaints of fixing impairment were in 9 (15.4%) patients: 4 (6.8%) with partial dentures and 13 (22.4%) with overdentures injury of oral tissues by the denture, was the cause of complaints in 12 (20.7%) patients: 7 (12.1%) partial and 5 (8.5%) overdentures. Conclusions. 1. Cause of half of the complications in patients with mandibular partial teeth loss that have removable dentures is diagnostic mistakes, that is caused by irrational choice of the treatment plan. 2. Effective methods to prevent complications is to consider diagnosis criteria of ICD-10 block K08.4 using clinical and laboratory protocols for comprehensive choice of the treatment plan in patients with mandibular partial teeth loss.